Racism in Europe: Characteristics and Intersections With Other Social Categories - Ball, Elena; Steffens, Melanie C.; Niedlich, Claudia (Frontiers in Psychology, 2022)
Concerning race and its intertwinements with gender, sexual orientation, class, accents, or ability there is a scarcity of social psychological research in Europe. With an intersectional approach studying racism in Europe it is possible to detect specific experiences of discrimination. The prevalent understanding of European racism is connected to migration from the former colonies to the European metropoles and the post-Second-World-War immigration of ‘guest workers.’ Thus, the focus of this research is on work-related discrimination. Against the background of a short historical review, we present the results of the few existing studies on intersectional discrimination within the labor market in Europe and discuss their implications. The pattern of findings is more complex than the assumption that individuals belonging to two or more marginalized social categories are always the most discriminated ones. Gender, sexual orientation, and origin rather interact with the specific job context. These interactions determine whether minority individuals are discriminated against or even preferred over individuals belonging to the majority group. We argue that considering the stereotype content model and social-identity theory helps to structure the sometimes contradictory results of intersectionality research. Therefore, the review presents new perspectives on racism in Europe based on current research, develops hypotheses on the interplay of intersecting identities, and identifies four novel research questions based on racist attributions considering situational variables: These are the role of concrete job contexts in explaining (no) discrimination, the influence of different stereotypes regarding marginalized groups, the explanatory value of sexual orientation as well as class or socioeconomic-status and age in terms of some patterns of results.